New Class of Competitive Inhibitor of Bacterial Histidine Kinases - Gilmour, Raymond (American Society for Microbiology, 2005)
Bacterial histidine kinases have been proposed as targets for the discovery of new antibiotics, yet few specific inhibitors of bacterial histidine kinases have been reported. We report here a novel thienopyridine (TEP) compound that inhibits bacterial histidine kinases competitively with respect to ATP but does not comparably inhibit mammalian serine/threonine kinases. Although it partitions into membranes and does not inhibit the growth of bacterial or mammalian cells, TEP could serve as a starting compound for a new class of histidine kinase inhibitors with antibacterial activity.